Entry strategies into biosimilars: assessment of entry modes into the field of biosimilars from the perspective of pharmaceuticals, generics and biologics companies - Von Gehren, August Levin (2013)
Today’s pharmaceutical industry is in transition. As major blockbuster drugs are losing or are about to lose patent protection, and big pharmaceutical companies are not replacing those products with new innovative chemical drugs, the industry looks for new fields of growth. One of these fields is the market for biosimilars which is being entered by pharmaceuticals, generics, and biologics companies. Even though the major market potential will awake around 2020, when important biological blockbusters lose patent protection, companies need to decide early whether they want to participate or not due to high technical entry barriers as well as long development timelines. As all companies come from different backgrounds, comprise different capabilities and have different entry incentives, the question arises whether these facts are related to their correspondent entry strategies. The thesis uses case studies from each segment of the pharmaceutical industry – pharmaceuticals, biologics, and generics – and examines through semi-structured interviews why the interviewed case study participants have explicitly chosen their entry strategy. The interview data will then be linked to strategic frameworks from the literature review and will be used for a comprehensive comparison and analysis. The study revealed that the background of the market entrant does influence its entry strategy. The main points of influence derive from both the entry barriers as well as the entry incentives. The thesis does not determine the possible future success of the analyzed entry mode within the new market.